Práticas de leitura numa perspectiva dialógica no ciclo de alfabetização: a Unidade de Educação Básica Poeta Gonçalves Dias - JESUS, Solange Cristina Campos de (2021)
The research presented in this dissertation refers to reading practices developed in a dialogic perspective for the readers’ education in the Literacy Cycle, aiming to verify the orientation of said practices at this level of education in collaboration with the pedagogical department in the Basic Education Unit. Poeta Gonçalves Dias, located in the municipality of Paço do Lumiar. The methodology is based on the theoretical methodological contributions of the historical-cultural approach and on bibliographic, documentary and field research: in the first, aided by authors such as Bakhtin (2016, 2011), Jolibert (1994), Goulart; Souza (2015), Mortatti (2000), Smolka (2012), Solé (1998), Voloshinov (2018) and Vygotsky (2007), among others; in the second, analyzing some documents that legitimize the educational policy, such as the Law of Directives and Bases of National Education (LDB), Law n.º 9394/96; the National Curricular Common Base (BNCC), the National Curriculum Parameters (PCN'S), as well as the school's Political Pedagogical Project; in the last one, the procedures that made it possible to carry out the investigation, using the semi-structured interview as a data collection instrument, which was applied via the Google Meet video tool (due to the restrictions imposed by the COVID-19 pandemic). A Notebook of Methodological Suggestions was prepared with a view to presenting didactic propositions based on a dialogic perspective to help teachers in the directions of teaching reading in the Literacy Cycle. It is concluded that the reading practices present in literacy classes are still rooted in the teaching of micro aspects of the language with emphasis on the relationship between graphemes and phonemes, despite the use of diversified textual genres, unlinking themselves from the reading practices present in the school to importance of children experiencing readings that privilege the meaning of texts through reading comprehension strategies; organization of moments that allow children to participate in real situations in the use of textual genres that circulate socially.